2014
DOI: 10.2478/s13386-013-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lime mortars and plasters from archaeological excavations in Hippos (Israel) using Electron Paramagnetic Resonance

Abstract: This study presents the preliminary results of investigation of the lime mortars and plasters from archaeological excavations in Hippos (Israel), using Electron Paramagnetic Resonance (EPR) spectroscopy. The research was conducted in order to characterize the building material and its reaction to ionizing radiation. The ancient settlement Hippos, situated on the east shore of the Sea of Galilee, functioned from the 3 rd cent. BC until it was destroyed by the earthquake in 749 AD. Lime mortars and plasters show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…These centers are detected in an EPR experiment, when the sample is placed in a homogeneous magnetic field and irradiated by a continuous flow of microwaves, which, when resonance condition is fulfilled, entails a transition between two spin states. (Grün 1991;Ikeya 1993Ikeya , 2004 Although the effects of γ radiation on calcium carbonate, especially in the form of calcite, has been investigated very thoroughly (Ikeya 1993(Ikeya , 2004Bahain et al 1994;Callens 1997;Callens et al 1998;Baїetto et al 1999;Polikreti et al 2004;Wencka et al 2005;Kabacińska et al 2017Kabacińska et al , 2019, to our knowledge only our group has analyzed it in lime mortars, first on samples from Sveta Petka church in Budinjak, Croatia (Kabacińska et al 2012), and later from ancient settlement Hippos, Israel (Kabacińska et al 2014b). In these studies, we found several signals generated in lime mortars by γ radiation and examined the dose response curves.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…These centers are detected in an EPR experiment, when the sample is placed in a homogeneous magnetic field and irradiated by a continuous flow of microwaves, which, when resonance condition is fulfilled, entails a transition between two spin states. (Grün 1991;Ikeya 1993Ikeya , 2004 Although the effects of γ radiation on calcium carbonate, especially in the form of calcite, has been investigated very thoroughly (Ikeya 1993(Ikeya , 2004Bahain et al 1994;Callens 1997;Callens et al 1998;Baїetto et al 1999;Polikreti et al 2004;Wencka et al 2005;Kabacińska et al 2017Kabacińska et al , 2019, to our knowledge only our group has analyzed it in lime mortars, first on samples from Sveta Petka church in Budinjak, Croatia (Kabacińska et al 2012), and later from ancient settlement Hippos, Israel (Kabacińska et al 2014b). In these studies, we found several signals generated in lime mortars by γ radiation and examined the dose response curves.…”
Section: Introductionmentioning
confidence: 92%
“…Full-range EPR spectra (650 mT magnetic field sweep) of investigated samples were previously shown and described in Kabacińska et al (2014b). They are characterized by a presence of common impurities-iron (g-factor values g a = 4.240 and g b = 2.032) (Ikeya 1993;Polikreti et al 2004) and manganese ions (Ikeya 1993;Baїetto et al 1999;Polikreti et al 2004).…”
Section: Identification Of Paramagnetic Centersmentioning
confidence: 99%
See 3 more Smart Citations